2022
DOI: 10.1007/s00426-022-01713-8
|View full text |Cite
|
Sign up to set email alerts
|

Element-level features in conjoint episodes in dual-tasking

Abstract: The usual way of thinking about dual-tasking is that the participants represent the two tasks separately. However, several findings suggest that the participants rather seem to integrate the elements of both tasks into a conjoint episode. In three experiments, we aimed at further testing this task integration account in dual-tasking. To this end, we investigated how the processing of the previous Trial n-1 shapes the processing of the current Trial n. We observed performance benefits when the stimulus–response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Unbeknownst to the participants, the marked screen locations follow a regular and repeating sequence. Implicit learning is a generally robust phenomenon (e.g., Reber, 1993 ). For instance, the meta-analysis of Oliveira et al ( 2023 ) found that reliability of the SRTT was not significantly affected by factors such as participants’ age, sequence type and variant of computing the index of procedural learning.…”
Section: Introductionmentioning
confidence: 99%
“…Unbeknownst to the participants, the marked screen locations follow a regular and repeating sequence. Implicit learning is a generally robust phenomenon (e.g., Reber, 1993 ). For instance, the meta-analysis of Oliveira et al ( 2023 ) found that reliability of the SRTT was not significantly affected by factors such as participants’ age, sequence type and variant of computing the index of procedural learning.…”
Section: Introductionmentioning
confidence: 99%